A fluorescence resonance energy transfer probe based on functionalized graphene oxide and upconversion nanoparticles for sensitive and rapid detection of zearalenone. (July 2021) - Li, Yahui; Li, Yanxiao; Zhang, Di; Tan, Weilong; Shi, Jiyong; Li, Zhihua; Liu, Hanyu; Yu, Yinyin; Yang, Liu; Wang, Xin; Gong, Yunyun; Zou, Xiaobo
Abstract: A precision strategy was successfully developed for the detection of zearalenone (ZEN) in maize. High-efficiency upconversion nanoparticles (UCNPs) were synthesized and used as the signal probe after conjugation with the oligonucleotides of ZEN aptamers. Graphene oxide modified with carboxyl groups [functionalized graphene oxide (FGO)] was used as a fluorescence quencher. When UCNPs and FGO were at distances less than 10 nm, fluorescence quenching based on fluorescence resonance energy transfer (FRET) was often noticed. Therefore, an upconversion fluorescent probe developed on the basis of FRET could detect ZEN in a short time. The results indicated that the correlation between the concentration of ZEN and the fluorescence intensity had a high relevance ( R 2  = 0.9985) in the range of 0.005–100 ng/mL. However, the detection limit was lower than those of the current methods. Moreover, the dependability of the fluorescent probe was confirmed by the results obtained in real samples. The results suggest that the novel upconversion fluorescent probe has great potential in the sensitive and rapid determination of ZEN. Highlights: Upconversion nanoparticles (UCNPs) were synthesized with good fluorescent property. A UCNPs probe was developed for sensitive and rapid detection of zearalenone. Application in real samples of this UCNPs probe has achieved excellent results. The UCNPs probe can be further used to detect other cereal/feed grains.